مسوغات التقديم والتأخير في سورة البقرة (University of Mosul-college of Basic Education, 2010)
اهتم النحاة بالتقديم الذي يمثل بؤرة الأسلوب الذي يدور حوله التركيب قيما يتعلق بترتيب الأجزاء داخل الجملة ، وإن أي تغيير يطرأ على الجملة من حيث تنظيم الكلمات او ترتيبها ينبني على معنى وهو ما يعنى به علماء النحو والبلاغة ، اذ يحدث التقديم فيه طلباً لإظهار ترتيب المعاني في النفس ، فقد يرد التقديم لأغراض عدة منها السبق في الزمان ، الاهتمام ، الاختصاص ، تقوية حكم وتأكيده ... الخ وهذا التقديم يؤثر في توجيه الدلالة لتغيير السياق لان فضيلة البيان لا تعود إلى اللفظ من حيث اللفظ وإنما تعود إلى النظم وترتيب الكلام وفق ترتيب معانيه في النفس .Grammarians paid a good attention to forwarding, which represents the focus of style, upon which the construction revolves concerning arrangement of words of a sentence, that any change in a sentence - in terms of arrangement of the words - may indicate another meaning; and this what the grammar and rhetoric scholars are concerned with. Forwarding is done to reveal the arrangement of meanings for the receiver. This forwarding might be used for many purposes; such as precedence in time, interest, specialization and emphasizing and strengthening certain grammatical or rhetoric rule,...etc. Forwarding influences the direction of the semantic meaning in changing the context, because the virtue of the eloquence doesn't relate to the sole utterance but it relates to the organization and arrangement of the speech depending on the arrangement of its meanings and their influence on the soul.